¬¬¬¬¬¬Amelioration of Colitis from Nature and its Immunological Implications: Current and Future Perspectives - Emmanuel Oluwaseun Adediran; Prabha S. Awale; Udai P. Singh (Lorestan University of Medical Sciences, 2022)
Inflammatory Bowel Disease (IBD) is a chronic immune-mediated inflammatory condition of the intestine. IBD is characterized by abdominal pains, diarrhea, fever, chills, cramps, and bloating and if not properly managed, it can be life-threatening. Interestingly, medicinal plants have been identified and validated to attenuate this condition due to the presence of natural products using different animal models via aryl hydrocarbon receptor and Adenosine 5'-monophosphate (AMP)-activated protein kinase (AMPK) signaling pathways. This review briefly discusses some of the natural products and medicinal plants, that can be used and developed as therapeutics for IBD treatment coupled with their immunological consequences. It recommends the need to use computational approaches to identify novel targets as well as the synthesis of structural analogs of endogenous ligands and natural products that are modulators of the identified and novel molecular targets coupled with the profiling of their biological activities and side effects.